Frequent epigenetic alterations in polycomb repressive complex 2 in osteosarcoma cell lines - Feng, Helin (Oncotarget, 2018)
Osteosarcoma (OS) cell lines are widely used in understanding the biological functions of cancer, identification and validation of therapeutic targets, as well as in vitro or in vivo preclinical drug screening. Here we report there is a frequent loss-of-function of polycomb repressive complex 2 (PRC2) in OS cell lines but it is rare in tumor samples based on genomic sequencing data, western blotting and immunohistochemistry analysis of H3K27me3. U2OS and 143B cell lines have a complete loss of function of PRC2 and several others have partial loss. In OS tumor tissues, only 1 out of 14 has low expression of H3K27me3. Kaplan-Meier analysis indicates that high EZH2, the component of PRC2, is associated with poor metastasis-free survival. Our observations are to raise the alarm that particular caution should be taken when using OS cell line models to study the disease, functional genomics, therapeutic target validation, drug screening, and epigenetic studies. Nevertheless, these cell lines will become useful biological tools to dissect the functions of PRC2.